Aggregation of Gel-Filtered Guinea-Pig Platelets by Lipoproteins - Fujitani, Buichi; Tsuboi, Toshimichi; Yoshida, Kouichi; Shimizu, Masanao (Thrombosis and Haemostasis, 1979)
Very low density lipoproteins (VLDL) and low density lipoproteins (LDL) were isolated from serum of hypercholesterolemic guinea-pigs, and the effect of these lipoproteins on guinea-pig platelets was studied. VLDL (>100 μg/ml) and LDL (>100 μg/ml) were found to cause aggregation of gel-filtered platelets (GFP), although the extent of GFP aggregation by LDL was smaller than that by VLDL. In platelet-rich plasma, however, lipoproteins could not induce platelet aggregation. VLDL and LDL even at the low concentrations at which lipoproteins alone could not induce aggregation potentiated ADP-induced aggregation of GFP. VLDL-induced aggregation of GFP was inhibited by apyrase (0.2–1.0 mg/ml) in a concentration-related manner. Prostaglandin E1, dipyridamole, potassium cyanide and ethylenediaminetetraacetic acid inhibited VLDL- and ADP-induced aggregation of GFP in the almost same degree. Inhibitions of VLDL-induced GFP aggregation by acetylsalicylic acid and albumin were slightly stronger than that of ADP-induced aggregation. These findings suggest that lipoproteins modulate platelets so that endogenous ADP can be released from platelets.